2013
DOI: 10.3109/02770903.2013.834505
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and severity of 2009 novel H1N1 influenza: a population-based case–control study

Abstract: Background Asthma has been shown to be associated with an increased risk of the 2009 novel H1N1 influenza (H1N1) infection among children. However, little is known about the role of asthma in severity of H1N1 infection. Objective To determine the association between asthma and other atopic conditions and severity of H1N1 infection. Patients and Methods We conducted a population-based case-control study. Cases were all Olmsted County, MN residents admitted to the hospital within a week of a positive test fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In the review of studies that provided estimates adjusted for the presence of other factors known to impact the risk of hospital admission for people ill with influenza, we found similarly heterogeneous estimates. There were no adjusted estimates that were significantly and consistently (across studies) outside the confidence bounds of the estimated pRR from this meta‐analysis …”
Section: Resultsmentioning
confidence: 85%
“…In the review of studies that provided estimates adjusted for the presence of other factors known to impact the risk of hospital admission for people ill with influenza, we found similarly heterogeneous estimates. There were no adjusted estimates that were significantly and consistently (across studies) outside the confidence bounds of the estimated pRR from this meta‐analysis …”
Section: Resultsmentioning
confidence: 85%
“…The increase in hospitalization among asthmatics may be attributed to a variety of factors including altered health seeking behavior (and in parents of asthmatics), heightened awareness due to media coverage, accelerated triage, and elevated physician precautions. Comparative analyses between seasonal and pandemic influenza concluded that the frequency of hospitalization and death as well as the profile of common underlying diseases, including asthma, were actually similar ( 116 119 ) although pH1N1 infections induced more severe disease in older age groups ( 120 ) and those with poorly controlled asthma ( 121 ) compared to seasonal strains. Therefore, greater attention to underlying diseases as risk factors during Swine Flu may have been due to the fact that pH1N1 induced more morbidity and mortality compared to the seasonal influenza virus strains that preceded it.…”
Section: Asthma and The 2009 Swine Flu Pandemicmentioning
confidence: 99%
“…The age of onset and endotype often determines the chronicity of asthma and maintenance medication use. Patients that were not on long-term therapeutics to control asthma symptoms had a higher incidence of pH1N1 infection ( 120 , 121 , 134 , 135 ). While the pH1N1 virus did increase the number of asthma exacerbations compared to seasonal strains ( 126 ), virus infection did not correlate to the severity of asthma symptoms ( 126 ).…”
Section: Asthma and The 2009 Swine Flu Pandemicmentioning
confidence: 99%
“…55 Other studies reported both an increased risk of H1N1 infection among children with other atopic conditions (adjusted OR, 1.89; 95% CI, 1.15-3.12) 56 and more severe H1N1 infection (risk of hospitalization) among those with than without asthma (matched OR, 2.31; 95% CI, 1.13-4.73). 57 Two independent studies identified asthma as the single most common comorbid condition among patients with severe H1N1 infection (hospitalization or death), with rates of asthma ranging from 10% to 32%. 58-61 …”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionsmentioning
confidence: 99%